ANALISIS KRITERIA PELAYANAN HOTEL DI KOTA BATAM - Sahrinuddin, Sahrinuddin; Nofriani Fajrah (Computer Science and Industrial Engineering, 2024)
One of the accommodations that is needed to support tourism is the availability of hotelsor inns. This is what makes entrepreneurs, especially in the field of hospitality, compete todevelop their business to attract visitors. ABC Resort is one of the companies engaged inthe accommodation sector which is most attractive to domestic and foreign touristsbecause of its location on the seafront directly adjacent to the Singapore Strait. Thepurpose of this study is to identify and analyze the standard criteria of hotel services inBatam city based on the hotel classification. The data obtained from the Voice of Customer(VoC) questionnaire will then be used as a guide in building the House of Quality (HoQ).Based on the calculation of the House of Quality (HoQ), it is known that there are 5 criteriafor service characteristics that have the highest priority value, namely the Hotel has aRestaurant and Bar with a Relative Importance Rate (TKR) value of 11%, Gym facilities,spa massage and sports healing with a TKR value of 10.2%, Availability of clean toilet andbathroom facilities with a TKR value of 8.84%, Luxury hotel buildings with a TKR value of6.55% and Interior and exterior design with a TKR value of 5.66%.